Covalent transfer of heavy chains of inter-alpha-trypsin inhibitor family proteins to hyaluronan in in vivo and in vitro expanded porcine oocyte-cumulus complexes - Nagyova, Eva; Camaioni, Antonella; Prochazka, Radek; Salustri, Antonietta (Biology of reproduction, 2004)
Previous studies have shown that the heavy chains (HCs) of serum-derived inter-alpha-trypsin inhibitor (IalphaI) molecules become covalently linked to hyaluronan (HA) during in vivo mouse cumulus expansion and significantly contribute to cumulus matrix organization. Experiments with mice suggest that the incorporation of such proteins in cumulus matrix appears to be rather complex, involving LH/hCG-induced changes in blood-follicle barrier and functional cooperation between cumulus cells, granulosa cells, and oocyte within the follicle. We demonstrate here that HC-HA covalent complexes are formed during in vivo porcine cumulus expansion as well. Western blot analysis with IalphaI antibody revealed that follicular fluids from medium-sized follicles and those from large follicles unstimulated with hCG contain high levels of all forms of IalphaI family members present in pig serum. The same amount of HCs were covalently transferred from IalphaI molecules to HA when pig oocyte-cumulus complexes (OCCs) were stimulated in vitro with FSH in the presence of pig serum or follicular fluid from unstimulated or hCG-stimulated follicles. In addition, HC-HA coupling activity was stimulated in cumulus cells by FSH treatment also in the absence of oocyte. Collectively, these results indicate that IalphaI molecules can freely cross the blood follicle barrier and that follicular fluid collected at any stage of folliculogenesis can be successfully used instead of serum for improving OCC maturation. Finally, pig cumulus cells show an autonomous ability to promote the incorporation of IalphaI HCs in the cumulus matrix.
Keywords: Follicular Fluid; Blood; Ovarian Follicle; Chorionic Gonadotropin; injekce; Tissue Culture Techniques; krev; Swine; Alpha-Globulins; choriogonadotropin; Oocytes; ovariální folikul; folikulární tekutina; ženské pohlaví; kyselina hyaluronová; zvířata; oocyty; Follicle Stimulating Hormone; Hyaluronic Acid; techniky tkáňových kultur; Injections; folikuly stimulující hormon; alfa-globuliny; prasata; Female; Animals